From seminary to university: an institutional history of the study of religion in Canada - Hughes, Aaron W. (University of Toronto Press, 2020)
"This book provides the first historical examination of the study of religion in Canada. While secular departments of religious studies would not emerge in Canada until the late 1960s, the teaching of religion under the guise of divinity, theology, the Bible, and moral philosophy has been omnipresent for much of the country's history. The gradual transformation from the teaching of religious truths at denominational theological colleges to the non-denominational and secular study of religion at universities was a lengthy and complicated one"